The mechanism of carbon source utilization by microalgae when co-cultivated with photosynthetic bacteria. (December 2022) - Shen, Xiao-Fei; Xu, Ya-Ping; Tong, Xiao-Qin; Huang, Qi; Zhang, Shuai; Gong, Jing; Chu, Fei-Fei; Zeng, Raymond Jianxiong
Graphical abstract: Highlights: Co-culture of proper PSB and microalgae enhanced biomass and oil productivities. Inoculation ratio affected the growth and oil productivity of co-culture. PSB promoted the microalgal metabolism of organic carbon utilization. PSB decreased the carbon dioxide utilization and photosynthesis of microalgae. Abstract: Microalgae-photosynthetic bacteria (PSB) co-culture, which is promising for wastewater treatment and lipid production, is lacking of study. In this work, the combinations of 3 microalgae and 3 PSB strains were firstly screened and then different inoculation ratios of the co-cultures were investigated. It was found the best promotion was Chlorella pyrenoidosa/Rhodobacter capsulatus co-culture (1:1), where the biomass productivity, acetate assimilation rate and lipid productivity were 1.64, 1.61 and 2.79 times than that of the sum of pure microalgae and PSB cultures, respectively. Meanwhile, the inoculation ratio significantly affected the growth rate and lipid productivity of co-culture systems. iTRAQ analysis showed that PSB played a positive effect on acetate assimilation, TCA cycle and glyoxylate cycle of microalgae, but decreased the carbon dioxide utilization and photosynthesis, indicating PSB promoted the microalgae metabolism of organic carbon utilization and weakened inorganic carbon utilization. These findings provide in-depth understanding of carbon utilization in microalgae-PSB co-culture.